Companies and Bank lending in Peru: 2009 - 2012 - Cortez Cortez, Gaby (2014)
The paper seeks to find the factors that influence corporate borrowing, taking as example a set of extractive and manufacturing companies listed on the Lima Stock Exchange. According to the hypothesis and the results of the econometric and statistical evaluation it has been able to establish the existence of a negative relationship between profitability and leverage of this group of companies. The average rate of return of the companies analyzed in the sample is 9.7 percent. Companies with higher negative elasticities show lower rates of return. Companies with lower negative elasticities show rates of return below average performance.